Multiple Perspectives of Conceptual Change in Science and the Challenges Ahead - Treagust, David F.; Duit, Reinders (Journal of Science and Mathematics Education in Southeast Asia, 2009)
Conceptual change views of teaching and learning processes in science, and also in various other content domains, have played a significant role in research on teaching and learning as well as in instructional design since the late 1970s. Conceptual change can be interpreted from different individual perspectives or from multiple perspectives. In the classical epistemological perspective, cognitive outcomes predominate whilst a multiple perspective can include both cognitive and affective outcomes. In this article we refer to the interpretation of conceptual change from a multiple perspective when an analogy was used in teaching optics. Here is evidence of the potential of a significant improvement in instructional practice. However, it becomes also evident that actual practice is far from what conceptual change perspectives propose and that change of this practice continues to be a rather difficult and long-lasting process. In this article, five challenges for future research and development in conceptual change at theoretical, methodological and practical levels are identified with a deliberate emphasis on their contribution to improve instructional practice.